(untitled) (International relations and international law Journal, 2016)
This article is an attempt to prove a global role of NATO in the contemporary international relations. Created in the period of “cold war”, the North Atlantic Treaty Organization was organized as a multipurpose institute for international cooperation in the security sphere. The major task carried out by the Organization, was a preparation for possible invasion to the territory of Western European states by the hostile block of the Warsaw Treaty Organization, and also a reflection of such invasion. After the end of “cold war” and in conditions of a new world order formation the NATO couldn’t continue the existence in the previous form. The organization was put before need “to create itself anew” in order to reserve a place in global security architecture of a new era. Therefore, in 1980-1990 NATO has begun a long period of transformation in the course of which there are a number of stages. First of all, these stages are connected with the evolution of North Atlantic alliance that can easily be tracked through the analysis of the three Strategic concepts accepted by NATO since 1991 and which are the reflection of an idea of NATO ’s global role in the contemporary world politics.